From co-regulation to self-regulation: maternal soothing strategies and self-efficacy in relation to maternal reports of infant regulation at 3 and 7 months - Kiel, Natalie; Şamdan, Gizem; Wienke, Annika S.; Reinelt, Tilman; Pauen, Sabina; Mathes, Birgit; Herzmann, Charlotte (Infant mental health journal, 2024)
This study, conducted in Germany, examines the role of maternal soothing strategies to explain the association of maternal self-efficacy with infant regulation (crying and sleeping behavior). Questionnaire data of 150 mothers, living in Germany, with mixed ethnic and educational backgrounds were collected when infants were 3 and 7 months old. Two types of maternal soothing strategies were distinguished: close soothing, involving close physical and emotional contact, and distant soothing, involving physical and emotional distancing from the infant. A cross-sectional SEM at 3 months indicated that maternal self-efficacy is associated with reported infant regulation through distant soothing strategies. Low maternal self-efficacy was associated with frequent maternal use of distant soothing, which in turn was related to reported infant regulation problems, that is, non-soothability and greater crying frequency. Frequent use of close soothing was associated with reported infant sleeping behavior, that is, frequent night-time awakenings. A longitudinal SEM further indicated that the effects of close soothing persisted at least until the infants' age of 7 months. The study showed how low maternal self-efficacy, increased use of distant soothing, and reported early infant regulation problems are intertwined and that, due to their persisting positive effect on infant soothability, close soothing better supports infant development.